Some extensions of Chu's formulas and further combinatorial identities - Said Zriaa; Mohammed Mouçouf (Mathematica Bohemica, 2024)
We present some extensions of Chu's formulas and several striking generalizations of some well-known combinatorial identities. As applications, some new identities on binomial sums, harmonic numbers, and the generalized harmonic numbers are also derived.